Function of E-protein dimers expressed in catfish lymphocytes - Hikima, Jun-ichi (2007)
E-proteins are essential class I bHLH transcription factors that play a role in lymphocyte development. In catfish lymphocytes the predominant E-proteins expressed are CFEB (a homologue of HEB) and E2A1, which both strongly drive transcription. In this study the role of homodimerization versus heterodimerization in the function of these catfish E-proteins was addressed through the use of expression constructs encoding forced dimers. Constructs expressing homo- and heterodimers were transfected into catfish B cells and shown to drive transcription from the catfish IGH enhancer. Expression from an artificial promoter containing a trimer of μE5 motifs clearly demonstrated that the homodimer of E2A1 drove transcription more strongly (by a factor of 10–25) than the CFEB homodimer in catfish B and T cells, while the heterodimer showed intermediate levels of transcriptional activation. Both CFEB1 and E2A1 proteins dimerized in vitro, and the heterodimer CFEB1-E2A1 was shown to bind the canonical μE5 motif.